The Spatialization of Saintly Memory: Barakah and the Transformation of Hawl Ritual in Rural Madura - Masruroh, Hullatul; Al Hashas, Mohammad Nasih; Nurkhalis, Nurkhalis; Thalal, Muhammad; Alfadhli, Alfadhli; Arsal, Fathur Riyadhi (Postgraduate Studies of UIN Sunan Ampel Surabaya, Indonesia, 2026)
This article examines the transformation of ḥawl rituals in rural Madura through an ethnographic study of the ḥawl of Pujhu’ Karang in Aeng Reksa Village, Lembana District, Sumenep Regency. It responds to studies that frame ḥawl mainly as a ritual formation of genealogical and hagiographic memory around saints or sacred lineages. Drawing on participant observation, semi-structured interviews with religious figures, committee members, and local residents, as well as documentation of the 2025 ḥawl, this article argues that the memory of Pujhu’ Karang is sustained not through manāqib, genealogy, or extended biography, but through grave space, congkop, local naming, tahlīl, ṣalawat, preaching, and the pursuit of barakah. The ḥawl thus shifts from genealogical remembrance to a communal-spatial ritual. This finding shows that local sainthood can be produced through place, ritual repetition, communal participation, and village religious identity, even when historical knowledge of the commemorated figure remains fragmentary, unstable, and orally transmitted.